ATP-Dependent Chromatin Remodeling Complex in the Lineage Specification of Mesenchymal Stem Cells - Wen Du; Daimo Guo; Wei Du (Stem Cells International)
Mesenchymal stem cells (MSCs) present in multiple tissues can self-renew and differentiate into multiple lineages including the bone, cartilage, muscle, cardiac tissue, and connective tissue. Key events, including cell proliferation, lineage commitment, and MSC differentiation, are ensured by precise gene expression regulation. ATP-dependent chromatin alteration is one form of epigenetic modifications that can regulate the transcriptional level of specific genes by utilizing the energy from ATP hydrolysis to reorganize chromatin structure. ATP-dependent chromatin remodeling complexes consist of a variety of subunits that together perform multiple functions in self-renewal and lineage specification. This review highlights the important role of ATP-dependent chromatin remodeling complexes and their different subunits in modulating MSC fate determination and discusses the proposed mechanisms by which ATP-dependent chromatin remodelers function.